Pengembangan Media Papan Berpeluang Untuk Meningkatkan Minat Siswa - Dhian Afrida Muthia; Pargito Pargito; Pujiati Pujiati (Jurnal Studi Sosial / Journal of Social Studies, 2017)
The purpose of this research is to produce an effective learning media board opportunities effective can interest student learning. The research development consists of five stage. The first stage is needs analysis consisting of preliminary observations and curriculum analysis. The second phase development model consisting of the development of blue print, flowchart, story board, lesson plans, and teaching of materials supporting. The third stage which consists of media design test expert validation of the people who expert in civic and the expert in learning. The fourth stage is products revision. The fifth is limited and the preparation of reports. Products the end of the study it will be instructional system or steps learning applied to implementation plan learning with the result that; (1) products board opportunities wonder that successfully developed can be used in learning civic education in the class VIII SMP Negeri 1 Natar Lampung Selatan, and (2) the media learning board opportunities effective in interest student learningTujuan penelitian ini adalah menghasilkan media pembelajaran efektif yang dapat meningkatkan minat belajar siswa. Penelitian pengembangan ini terdiri dari lima tahap. Tahap pertama adalah analisis kebutuhan yang terdiri dari observasi awal dan analisis kurikulum. Tahap kedua pengembangan model yang terdiri dari pengembangan blue print, flowchart, story board, RPP, dan bahan ajar pendukung. Tahap ketiga uji ahli yang terdiri dari ahli materi PKn dan ahli desain media pembelajaran. Tahap keempat revisi produk. Tahap kelima uji terbatas dan penyusunan laporan. Produk akhir penelitian ini berupa sistem instruksional atau langkah-langkah pembelajaran yang diaplikasikan dalam Rencana Pelaksanaan Pembelajaran dengan hasil bahwa; (1) produk media pembelajaran papan berpeluang yang berhasil dikembangkan dapat digunakan dalam pembelajaran PKn dan (2) media pembelajaran papan Berpeluang efektif dalam meningkatkan minat belajar siswa.Kata kunci: media pembelajaran papan berpeluang, minat belajar, pembelajaran PKn, pengembangan